Classified ebook - Michaels, Fern (Godmothers, 2013)
#1 New York Times -Bestselling Author: "Whoever thought the 'golden years' were boring never met the Godmothers."— RT Book Reviews The riches that mean most to Teresa "Toots" Loudenberry are the loving friends and family she's accumulated over the course of a life well lived. And now that her daughter, Abby, has married her beau Chris and settled down near Toots in Charleston, life is even more satisfying than the delicious pralines sold at Toots's bakery, The Sweetest Thing. Abby isn't the only one enjoying a little romance. Toots's friendship with Dr. Phil Becker has grown unexpectedly close . . . and that brings both joy and complications. As a distraction, Toots throws herself into helping Abby and Chris open an animal rescue shelter on their estate. But life takes a serious turn when two young children disappear after visiting The Sweetest Thing. Toots immediately enlists Ida, Sophie, and Mavis to help in the search. As they draw closer to the culprits, they realize the stakes are much higher than they ever could have imagined . . . "Grab some tissues as you read the latest installment of the outstanding Godmothers series, which contains an abundance of poignancy, wit, charm and laugh-out-loud moments. Reading Michaels is always a rewarding experience." — RT Book Reviews "Michaels' engaging version of the Golden Girls."— Booklist